Total Body Irradiation (TBI) in pediatric patients - Linsenmeier, Claudia; Thoennessen, Daniel; Negretti, Laura; Bourquin, Jean-Pierre; Streller, Tino; Lütolf, Urs Martin; Oertel, Susanne (Strahlentherapie und Onkologie, 2010)
To retrospectively analyze patient characteristics, treatment, and treatment outcome of pediatric patients with hematologicdiseases treated with total body irradiation (TBI) between 1978 and 2006.
Gesehen am 28.03.2023